"New Extractivism" in Mexico: Hope and Deception. Issue 2 (August 2018) - Holland, D. Lynn
This paper traces the evolution of mining law in Mexico, including the most recent round of reform, and discusses the social and environmental impacts of mining in the region of Soconusco in the state of Chiapas. A set of mining reforms that passed between 2013 and 2014 provided the necessary impetus for a rise in mining investments in Mexico. These reforms have been couched in the language of "new extractivism." In this approach favored by the left, extractivism is embraced as a development strategy along with the goal of redistributing some of the revenues to rural areas where these activities take place. In addition, these communities are to be consulted on how the funds will be spent. As fortunes have been made, however, the results have fallen short where environmental protection and community support are concerned.